Perbedaan Psychological Well-Being Pada Penderita Diabetes Tipe 2 Usia Dewasa Madya Ditinjau Dari Strategi Coping - Titi Angraeni (2012)
This research aimed to find out if there any difference of psychological well-being on middle age adult with type 2 diabetes based on coping strategy. Psychological well-being is a positive character ownership on self-acceptance, positive relation with others, autonomy, enviromental mastery, purpose in life and personal growth. Coping strategy referred in this research is problem-focused coping and emotion-focused coping. This research carried out in Poli Penyakit Dalam at RSUD Sidoarjo with number of the subject as much as 40 people including 21 male and 19 female who has type 2 diabetes and are at the age of 35-60 years old. Sampling in this research is carried out by incidental sampling techniques. To collecting data using form of questionnaire which adapt from Ryff’s Psychological Well-Being Scale with 42 items and COPE Scale as much as 40 items. Reliability is 0,768 for the scale of psychological well-being and to scale coping strategy is 0,944. Data analysis was conducted with statistical techniques distinction independent sample t-test with the help of statistics programs SPSS version 16.0 for windows. The results of a statistical analysis produce value of t=0,432 with p=0,668 (p > 0,05). This result shows that there was no difference in psychological well-being on middle age adult with type 2 diabetes based on coping strategy.